2015
DOI: 10.1002/2014gb004985
|View full text |Cite
|
Sign up to set email alerts
|

Flux and budget of BC in the continental shelf seas adjacent to Chinese high BC emission source regions

Abstract: This study conducted the first comprehensive investigation of sedimentary black carbon (BC) concentration, flux, and budget in the continental shelves of "Bohai Sea (BS) and Yellow Sea (YS)," based on measurements of BC in 191 surface sediments, 36 riverine water, and 2 seawater samples, as well as the reported data set of the atmospheric samples from seven coastal cities in the Bohai Rim. BC concentrations in these matrices were measured using the method of thermal/optical reflectance. The spatial distribu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
100
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 66 publications
(112 citation statements)
references
References 79 publications
10
100
2
Order By: Relevance
“…Therefore, it is worth noting that the direct comparison as noted above was complicated considering the used different BC quantification methods with regard to the BC sources and sinks. Anyway, based on the same BC measurement procedures, the mass inventory of BC in the GOT in the present study was comparable with our recent work in the Bohai Sea (~147 Gg/y) and the Yellow Sea (~171 Gg/y) off the western Pacific margins (Fang et al, 2015). The semi-enclosed Bohai Sea and Yellow Sea, from the moderatehigh latitude region, are mainly situated at the downwind area of the East Asian Monsoon, receiving large amounts of combustionderived substances (e.g., PAHs) through atmospheric deposition, especially in the winter season due to the extensive regional heating activities in China (Wang et al, 2014).…”
Section: Mass Inventory Of Bc In the Got Sediments And Its Comparisonsupporting
confidence: 91%
See 4 more Smart Citations
“…Therefore, it is worth noting that the direct comparison as noted above was complicated considering the used different BC quantification methods with regard to the BC sources and sinks. Anyway, based on the same BC measurement procedures, the mass inventory of BC in the GOT in the present study was comparable with our recent work in the Bohai Sea (~147 Gg/y) and the Yellow Sea (~171 Gg/y) off the western Pacific margins (Fang et al, 2015). The semi-enclosed Bohai Sea and Yellow Sea, from the moderatehigh latitude region, are mainly situated at the downwind area of the East Asian Monsoon, receiving large amounts of combustionderived substances (e.g., PAHs) through atmospheric deposition, especially in the winter season due to the extensive regional heating activities in China (Wang et al, 2014).…”
Section: Mass Inventory Of Bc In the Got Sediments And Its Comparisonsupporting
confidence: 91%
“…The blank samples (n ¼ 10) yielded 0.00 ± 0.00 mg/cm 2 for BC, and the RSD of 10 pairs of replicate analyses was in the range of 0e11%, and averaged within 5%. The BC concentration measured in SRM 1941b was 10.56 ± 1.28 mg/g (n ¼ 10), which was well in accordance with the values reported by recent studies (Hammes et al, 2007;Han et al, 2007a;Cong et al, 2013;Fang et al, 2015). These QA/QC results suggested that the BC analytical method used here was credible and repeatable (see Supplementary materials).…”
Section: Analytical Proceduressupporting
confidence: 90%
See 3 more Smart Citations